Forecasting mode choice of private car and transport network vehicle service users considering the Metro Manila bus rapid transit-line 1 - Cua, Jose Alfonso Maria C.; Diaz, Crispin Emmanuel D. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
This study chiefly examined the probability of private car and transport network vehicle service (TNVS) users shifting to the bus rapid transit (BRT) system along the Quezon Avenue-España Boulevard corridor given a range of time and cost savings offered by the Metro Manila BRT - Line 1 system, which the Department of Transportation had planned to implement along aforesaid corridor. Chosen respondents were those who ply any portion of this corridor at least once a week using a private car, TNVS or both. Surveys were conducted personally and online. The former were done in five key areas located within or near the corridor. Respondents were classified into different groups according to their mode usage and survey location. Each group was further dichotomized into subgroups based on four socioeconomic characteristics: gender, occupation, civil status, and education. The researcher used data from the surveys to generate models that focused on two variables, travel time saving, using binary logistic regression. The researcher then derived the probabilities from the models given various scenarios containing a combination of travel time and cost savings. Groups selected for analyses were only those that generated pairs of models with excellent or good fit. The analyses of this study indicated that female respondents or non-working respondents generally had higher probabilities of shifting to the than their counterparts who are male working respectively. Single respondents had a higher probability of using the BRT than their married counterparts, but the indication is relatively weak. The results for respondents with at most a bachelor's degree and those with above a bachelor's degree gave no clear and general indication who between them had a stronger or weaker reception to using the BRT. Income, age, car ownership frequency of use of private cars or TNVS, travel distance, and travel time could mainly be associated with the respondent's propensities to shift. Based on the results of this study, general policy recommendations included a segmented fare scheme (e.g. lower fares for students) and a special consideration for women in the design of the service. It was also found that association for some variables - such as reliability, comfort, accessibility, and security - could not be confirmed. It is recommended that future studies include other factors and look into alternative framing and measurement to improve model specification.
Thesis (M.A Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Bus rapid transit -- Philippines -- Manila metropolitan area; Local transit -- Philippines -- Manila Metropolitan Area; Local transit accessibility -- Philippines -- Manila Metropolitan Area; Transportation -- Philippines -- Manila Metropolitan Area